Penggunaan Strategi Pembelajaran Modeled Talk untuk Meningkatkan Keterampilan Berbicara Bahasa Inggris Siswa Kelas VIII SMP - Meriastuti, Ni Made (Universitas Pendidikan Ganesha, 2018)
This research was motivated by the ability of grade VIII students of junior high school in learning English was still low especially in speaking skill. This study aims to improve English speaking skill of grade VIII students of junior high school by using Modeled Talk. The method used to collect data was the method of test and observation. the instruments used in data collection were test, observation sheet and questionnaire. The results of this study indicated that there was an improvement in students’ speaking skill, in which on the first cycle of this study the average score of the students’ speaking skill was 2.75 with the percentage of 64.2% and on the second cycle the average score of students’ speaking skill was 3.00 with percentage of 70.0% and the category is good. In cycle 1, the percentage of pronunciation was 65.8%, 65.8% for grammar, 68.3% for vocabulary, 60.0% for fluency and 60.8% for comprehension. Furthermore in cycle 2, there was an increase in each aspect such as: pronunciation of 70.8%, grammar of 72.5%, vocabulary of 69.2%, fluency of 67.5% and 70.0% for comprehension aspect. This study continues into cycle 2 because completeness classical of cycle 1 only 64.3% of students who were able the get the value equal to or more than 67 as the minimum criterion value. Furthermore, in cycle 2 occurs an increase for classical completeness that is 89.3%. Thus, it can be suggested that Modeled Talk can be used to improve the English speaking skill of grade VIII junior high school students.